An investigation of the current status of recycling spent lithium-ion batteries from consumer electronics in China. (10th September 2017) - Gu, Fu; Guo, Jianfeng; Yao, Xing; Summers, Peter A.; Widijatmoko, Samuel D.; Hall, Philip
Abstract: Ever-increasing demand and production of lithium-ion batteries result in disposal problems. There is little known information about recycling lithium-ion batteries from consumer electronics in China, despite China is the largest lithium-ion battery manufacturer and consumer. To address this gap, this paper aims at investigating the current status of recycling spent lithium-ion batteries from consumer electronics in China, and to provide recommendations for improving spent lithium-ion battery recycling rate. Generation, collection and recycling of spent lithium-ion batteries were investigated using a combined methodology consists of online surveys, field investigations and estimations. The survey shows that although respondents have expressed their willingness towards recycling, most of them did not know where to send their spent lithium-ion batteries. Field investigations were carried out to trace the material flow of spent lithium-ion batteries in current waste electric and electronic equipment collection systems. It was found that the spent lithium-ion batteries are not included in current collection systems, as only few recycling practitioners are collecting spent lithium-ion batteries. Inadequate supply was found to have a significant impact on current recycling industry. Combining official statistics, survey results and actual throughput of the recycling plants, it was roughly estimated that less than 10% of lithium-ion batteries used in consumer electronics are currently recycled, while others always end up in idle or landfill. This study provides essential information on status quo of recycling lithium-ion batteries from consumer electronics in China including consumers' behaviours, recycling practices and estimated recycling rate. Further, policy implications were proposed with the purpose of promoting recycling rates of spent LIBs from CEs. Highlights: People's disposal behaviours and attitudes on spent LIBs recycling are surveyed. Collecting spent LIBs is not included in the current WEEE collection systems. Inadequate supply of spent LIBs limits the throughputs of disposers. The current collection and recycling rates of spent LIBs are less than 10%. Policy implications are proposed to promote the recycling rates of LIBs.